ANALISIS KANDUNGAN ZAT PEWARNA RHODAMIN B PADA ARUM MANIS BERDASARKAN STATUS EKONOMI PENJUAL ARUM MANIS DI SEKOLAH DASAR KECAMATAN BABAT KABUPATEN LAMONGAN - Kartikorini, Nastiti (Universitas Muhammadiyah Surabaya)
ANALISIS KANDUNGAN ZAT PEWARNA RHODAMIN B PADA ARUM MANIS BERDASARKAN STATUS EKONOMI PENJUAL ARUM MANIS DI SEKOLAH DASAR KECAMATAN BABAT KABUPATEN LAMONGANIr. Nastiti K., M.Kes.nastitikartikorini@gmail.com Prodi D3 Analis Kesehatan UM SurabayaÂ AbstractKnowledge and economic status, including the factors that underlie the occurrence of certain behaviors. Low knowledge about food dyes potentially encourage traders using Rhodamine B as a food additive. Though dye Rhodamine B dye is additional consumer prohibited in food products. Based on the above can be taken formulation of the problem,